Architectural remains to the east of the Kumbheshwar Mahadev Temple complex - Temples of India Project Team (Jio Institute, 2024)
There are several architectural remains to the east of the Kumbheshwar Mahadev Temple complex. These were retrieved from the temple premises. The remains consist of pillars, lintels, plinth mouldings, shikhara (superstructure remains), pranala (water chute), among several others.